RELATING EFL LEARNERS’ GRAMMAR KNOWLEDGE TO THEIR USE OF PRAGMATIC EXPRESSIONS - Nida Husna (IJEE (Indonesian Journal of English Education), 2014)
When people use language as a tool to communicate, the meaning that is conveyed or received will be more than what is heard from the explicit utterances. It is believed that the language we use as the code can be interpreted in any meaning, which interpretation becomes part of pragmatics. Grammar ability and pragmatic competence should work together to create good communication and avoid misunderstanding. This paper presents three aspects. The first aspect is the kinds of pragmatic knowledge that the EFL learners may have about their foreign language they are learning. The second aspect is how the EFL learners use their foreign linguistic expressions in a contextually appropriate manner within their daily communication. The last one is to what extent the EFL learners understand the implicit messages of expressions.